1994
DOI: 10.1111/j.1460-9568.1994.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐spanning Behavioural and Adrenal Dysfunction Induced by Prenatal Hypoxia in the Rat is Prevented by the Calcium Antagonist Nimodipine

Abstract: The long-term behavioural effects of prenatal chronic anaemic hypoxia were investigated in young (5 months old), late adult (19 months) and aged Wistar rats (23-26 months). Sodium nitrite (2 g/l) offered in the drinking water during the second half of pregnancy served to evoke prenatal hypoxia. In parallel to nitrite treatment the Ca2+ channel blocker nimodipine (10 mg/kg) or vehicle alone was administered intragastrically once daily. Open-field activity, intermale social behaviour, learning ability in a black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…To our knowledge, few studies have investigated the social interaction following prenatal hypoxia. Corroborating our results, Nyakas et al (1994) reported that nitrite-induced hypoxia during the second half of pregnancy decreased the duration of social interactions in aged Wistar rats. Developing neurons are particularly susceptible to hypoxic-ischemic injury; however, brain damage and subsequent neurodevelopmental impairment depends on the severity, duration and repetition of the insult, as well as on the maturity and condition of the fetus (Gunn and Bennet 2009).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, few studies have investigated the social interaction following prenatal hypoxia. Corroborating our results, Nyakas et al (1994) reported that nitrite-induced hypoxia during the second half of pregnancy decreased the duration of social interactions in aged Wistar rats. Developing neurons are particularly susceptible to hypoxic-ischemic injury; however, brain damage and subsequent neurodevelopmental impairment depends on the severity, duration and repetition of the insult, as well as on the maturity and condition of the fetus (Gunn and Bennet 2009).…”
Section: Discussionsupporting
confidence: 76%
“…In fact, a number of epidemiological studies and rodent models have confirmed that hypoxic-ischemic insults disrupt normal brain development, with long-lasting behavioral, motor and cognitive implications (Tejkalova et al 2007), which represent a risk factor for mental retardation, attention-deficit/ hyperactivity disorder (ADHD), memory impairment and schizophrenia (Adriani et al 2006). In addition, there is evidence that prenatal hypoxia leads to a decrease in social contact in rats (Nyakas et al 1994). Taking all this information together, the aim of the present study was to verify the adult social behavior of offspring exposed to maternal convulsive seizures in utero.…”
Section: Introductionmentioning
confidence: 98%
“…Similar effects were observed using nimodipine (a well‐known calcium channel blocker). Oral daily administration of nimodipine (10 mg/kg) was able to prevent abnormal learning, social and emotional behavior impairments, as well as the stress response after prenatal hypoxia induced by sodium nitrate in the second half of gestation in Wistar rats suggesting that the reduction of excitotoxicity is an important pathway that could be modulated during pregnancy (Nyakas et al, 1994b).…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…Nimodipine is an L‐type Ca ++ channel blocker and has shown to penetrate through the placenta and consequently exert pharmacological action directly in the foetus. Nyakas et al (1994a,b) administered nimodipine in the food pellets during pregnancy and observed that the substance counteracted the anaemic‐cytotoxic hypoxia induced by sodium nitrite (2 g/l) administered in the drinking water during pregnancy. Nimodipine prevented the decrease in serotonergic and cholinergic nerve fiber growth in a region‐specific manner in the cortex as from 1 to 20 days post injury (Nyakas et al, 1994a).…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…The test was performed on the fifth postoperative day. Rats were positioned into the center of an open-field box consisting of a cylindrical arena of 80 cm in diameter, divided into 20 sectors by concentric and radial lines, and surrounded by a 35-cm-high wall [33]. During a 3-1min recording period, the number of lines crossed between sectors and the number and duration of rearings were scored.…”
Section: Orientation Response To Noveltymentioning
confidence: 99%